2017
DOI: 10.7554/elife.25328
|View full text |Cite
|
Sign up to set email alerts
|

The laminar organization of the Drosophila ellipsoid body is semaphorin-dependent and prevents the formation of ectopic synaptic connections

Abstract: The ellipsoid body (EB) in the Drosophila brain is a central complex (CX) substructure that harbors circumferentially laminated ring (R) neuron axons and mediates multifaceted sensory integration and motor coordination functions. However, what regulates R axon lamination and how lamination affects R neuron function remain unknown. We show here that the EB is sequentially innervated by small-field and large-field neurons and that early developing EB neurons play an important regulatory role in EB laminae format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 75 publications
2
44
0
Order By: Relevance
“…In Drosophila, this tethering is thought to come from a large population of inhibitory ring neurons (Hanesch et al, 1989;Homberg et al, 2018;Lin et al, 2013;Omoto et al, 2018;Xie et al, 2017;Young and Armstrong, 2010). However, this has not yet been verified experimentally.…”
Section: Ring Neurons Tether the Compass To Visual Scenes By Selectivmentioning
confidence: 99%
“…In Drosophila, this tethering is thought to come from a large population of inhibitory ring neurons (Hanesch et al, 1989;Homberg et al, 2018;Lin et al, 2013;Omoto et al, 2018;Xie et al, 2017;Young and Armstrong, 2010). However, this has not yet been verified experimentally.…”
Section: Ring Neurons Tether the Compass To Visual Scenes By Selectivmentioning
confidence: 99%
“…1c-h; Supplemental Video 3 show details of these structures and single-cell identities). The stratified organization of the nerve ring neuropil, resolved here at single neurite level, is reminiscent of laminar organizations in the Drosophila nervous system 42,43 , and in the vertebrate retina and the brain cortex 44,45 .We observed that not all computationally clustered neurites followed simple bundled paths through the neuropil. In Strata 1 (S1), 32 anterior sensory neurons project perpendicular to the nerve ring bundle before making a 180º curl and returning to the anterior limits of the neuropil, where they terminate as synaptic endplates (Fig.…”
mentioning
confidence: 57%
“…Overall, our analyses reveal design principles at varying degrees of granularityfrom single 'rich-club neuron' morphologies that functionally bridge different strata, to layered bundles that segregate sensory-motor information onto topological maps. These design principles are important organizational units in neuroscience-'rich-clubs' in the context of brain networks 18,21 , laminar organization in the context of brain structures [42][43][44][45] and topological maps in the context of vertebrate sensory systems [51][52][53] . We map them in the context of the neuropil architecture and resolve them for C. elegans at cellular and synaptic scales.…”
Section: Unassigned Cells Correspond To 'Rich-club' Interneurons Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…To address which ring neurons receive stimuli from TuBusup, we used high-resolution ExM imaging and confirmed that EB-R2/R4m neurons labeled by the R32H08-LexA show potent overlap with the TuBusup (Figure 6c) (Xie et al, 2017), other layers of EB ring neurons barely connect to that part of BUsup (data not shown). The data suggest that APDNs specifically activate TuBusup and then input to EB-R2/R4m neurons, which are essential for sleep and arousal regulation.…”
Section: Lexa >Lexaop-flp Uas-frt-stop-frt-cschrimson) Immunohistocmentioning
confidence: 91%